OLDER WOMEN AND INTEGRATING A GENDER PERSPECTIVE IN EMPLOYMENT POLICY (Law and world, 2023)
The main challenge in creating dignified living conditions for older women is employment. If the employment process of older women is not properly regulated, they will lose the opportunity to maintain their health and well-being. Unpaid domestic work and discriminatory stigmas have a major impact on employment. Social security, which appears in the form of a post-employment (funded or state) pension, determines the economic status of older/eldest women. Based on the above, the research on the issue of employment should include an analysis of the issue of stigmas, gender perspective and employment issues, hence proposing legislative changes to the state for favourable conditions for older women. In order to develop effective state policy, the article aims to analyse the international documents and the practice of the State of Israel to discuss the employment of elderly women in the central core of the state policy.Keywords: decent Living of older women, employment policy, discriminatory stigmas IntroductionBack in 1996, US Senator Carol Moseley-Braun of Illinois, in her essay "Women's Retirement Security”, noted that reducing the gender gap (index of disparity) and ultimately closing the disparity is essential to improving real retirement security.[1] In order to eliminate the mentioned difference, it is necessary to recognise the caregiving activity of women at the legislative level, and at the same time, the state should develop an effective pension policy in parallel with the employment process and the work process. Senator Carol has likened retirement security to a three-legged stool[2] - social security, private pensions, and personal savings form the basis for a person to receive income later in life. The democratic world, in the Universal Declaration of Human Rights adopted in 1948, loudly affirmed its belief and respect for basic human rights as a whole and highlighted human dignity and equality principle as one of the fundamental rights among other basic rights based on which every state strives to promote social progress and to create a better standard of living for the people and citizens within its jurisdiction.[3] "The Declaration has inspired many newly independent states and new democracies in the process of forming and creating constitutions. It is the criterion and measure of how we define, or how we should define, what is good and what is bad."[4] Decent living conditions are a broad concept that crosses several human rights articles at the same time and combines several values. In particular, the first article of the Universal Declaration states that all human beings are born free and equal in dignity and rights. The declaration's 22nd, 23rd, 24th, and 25th articles appear as reinforcing norms of dignity and dignified existence. The aforementioned articles protect both older women and people of any age and gender, and if we rely on Article 28, everyone has the right to a social and international order to exercise the freedoms mentioned in the declaration fully. In the state, the national government is obliged to implement such a state policy to eliminate discriminatory and unfavourable conditions among people.[5] The above-mentioned articles of the Universal Declaration of Human Rights combine several values and are significant. In particular, social security is a necessary factor for maintaining dignity, which includes the free and full development of a person, which is significantly violated in the presence of age and gender discrimination against older women. In addition, the unity of these values includes the rights to a favourable (supportive) working environment, dignified human existence (economic status), labour and unemployment protection, which elderly women cannot fully use in the presence of employment difficulty and an unregulated informal economy. Ultimately, according to Article 25 of the Declaration, everyone has the right to a standard of living adequate for their health and well-being. This includes both the period of unemployment and old age. However, if the employment process for older women is not fairly regulated, they will lose the opportunity to maintain their health and well-being. The main challenge in creating decent living conditions for older women is employment.[6] The purpose of the research is to analyse the international documents and the practice of the State of Israel to discuss the issue of employment of elderly (older) women in the main core of the state policy in order to develop effective state policy and legal regulations.Older women's employment, gender perspective, and discriminatory stigmasIt should be noted that unpaid domestic work and discriminatory stigmas have a major impact on employment. In addition, social security, which appears in the form of a post-employment (cumulative/private or state) pension, determines the economic situation of older women. Based on the above, research on the issue of employment should include an analysis of stigmas, gender perspectives, and employment.As noted in the INSTRAW publication “Ageing in Gendered World Women's Issues and Identities:" ageing, as a stage of development, is a challenge for women. In this period of life, women should be able to cope creatively with new opportunities. The social consequences of stereotyping elderly women should be recognised and eliminated. Subsequent meetings on ageing began to emphasise the integration of older persons into the life of society, regarding them not as a burden of productive members of society but as creative and productive members in their own right. Women, who because they live longer, represent the majority of older people in almost every country, are a particularly neglected resource in their elder years.”[7]According to international studies, women generally live longer than men due to biological and behavioural advantages, but women's longer lives do not necessarily mean healthier lives.[8] It is a fact that only women experience the potentially negative consequences and risks associated with the health and psychological state of pregnancy and childbirth. Further, existing gender inequality is expressed in terms of income and employment. The mentioned gender inequality originates from when a woman is devoted to childcare, child-rearing, and family work, and if we go deeper, the result of the mentioned time is the formation of the next generation. Moreover, in response, women remain discriminated against both from an economic point of view (less accumulated pension, less income, lower position) and a moral point of view. [9]A major challenge for health systems is likely to be meeting the needs of older women, as they live longer than men and represent a growing proportion of all older people.[10] “At first glance, longer life expectancy is no doubt a sign of progress, which is the result of increasing wealth and access to medical care all over the world according to relevant percentages. When you look at this picture from one point, it is tempting to think that the problem of women in poverty is gradually and moderately reduced, but unfortunately, this is a false impression. When you come closer and closer to this mosaic, you see a lot of problems regarding older women and a growing number of them without the growth of the economy and without changing the world's perception. Stereotypes bring devastating effects on older women and for the world as well.”[11] Therefore, the state should start preparing to prevent cases of age-related discrimination. Caring for older women involves not only strengthening the health system but also pension and tax reform, which includes access to employment and related pension and social protection. By creating conditions for an active, healthy life, older women will be allowed to participate fully in the development of society.Appropriate legal recognition of older women's labour resources, economic empowerment of older women, and reasonable access to public employment services may reduce gender inequality. According to the national legislation of Georgia, women of retirement age can be considered in the category of older (elderly) women. The retirement age for women in Georgia is set at 60 years.[12] The social security and state assistance of the State of Israel has a significant impact on the economic empowerment of older women. Israeli legislation recognises the contingent of unemployed women aged 50+ to 67 as vulnerable and a priority group for receiving benefits. The vision of the State of Israel in the development of financial support programs for older women, recognition of the rights of older women, and their regulation at the legal level can be appropriate for Georgia as well. By analysing the Israeli state policy regarding a specific age group of unemployed women, it is possible to define older women by age categories. It is worth noting several directions of social security and state assistance of the State of Israel:The right of unemployed women aged 57-67 to receive state financial assistance.[13] It is also important that those women who have completed professional training courses be encouraged by the high percentage of allowance. The state's financial support for unemployed women at a particular age, when their skills are undergoing transformation, is an excellent motivator for older women to create decent living conditions and feel like a necessary asset to society.[14]The state has an obligation to grant a pension to a 62-year-old female citizen. However, incentives (benefits) and assistance for elderly women are not cancelled for women who have reached the age of 67.As of January 2022, the amount of work and non-work income has increased, in which case an Israeli citizen will be able to simultaneously use old age benefits, which start after the retirement age, namely from 70 years.[15] As of today, the retirement age for women under Israeli law is 62, although there will be a gradual change in the retirement age for women from 62 to 66.[16]The National Insurance Institute pays monthly assistance to families with children under the age of 18. The allowance is aimed at helping families with the costs of raising children, and its amount does not depend on the family's income. This significantly helps women’s social and economic empowerment, easing their burden. If we rely on the reasoning that older women often become caretakers of young children in their families by their own will or by necessity due to a lack of financial resources, this allowance allocated by the Israeli state can be considered as respect, compensation, and recognition of their work by the state.[17]According to the March 20, 2023 interview of Mr Matan Hammou from the Israeli Ministry of Labor, that is the lead director of elderly employment (the person responsible for the advancement of special populations in the labour market) (recorded by scientist Irina Batiashvili), the analysis of the policy of employment of the elderly in Israel:Employment has far greater effects and various connections and should not be seen only as a source of income. An employed person considers himself an active member of society and does not aspire to actively receive social protection or actively use social and health services.The specificity of the issue of older women is related to the problem of "ageism", how employers look at the policy of hiring new staff. For example, we are looking for a young and energetic staff for a new and dynamic company. This means that as people get older, they are neglected, and at the same time, negative stigmas force the elderly to miss employment opportunities/earning opportunities. From the interview of the Senior Manager of Unique Populations Recruitment of the Ministry of Labor of Israel (Population Employment Administration, Work office), it can be seen that the percentage of employment of 45-year-olds is decreasing sharply. As people get older, it becomes harder for them to get back into the labour market. For example, if a young person can find a new job in 3-4 months, this opportunity becomes much more difficult for an older person. At the age of 54, there is a high probability that an unemployed, elderly person will not be able to return to the labour market. This affects part of the pensions because the pension system in Israel is similar to the accumulation system (the successive increase of the pension depends on the employee's percentage investment).Therefore, Israel decided to strengthen its employment policy and invest in reintegrating the elderly, especially older women, into the labour market. Israel, therefore, decided to invest in increasing employment opportunities for vulnerable groups. These policies have long-term effects on employees, employers, the health system, and social services.In addition, Israel's vision of the retirement age and related long-term policy is noteworthy, according to which in 2032, the gap between the retirement age of women and men will decrease, and in 2032, the retirement age of women will be set at 65 years and 67 years for men. This will help the country's employment policy. In this regard, Israel has developed a transitional mechanism, which includes training and employment of older women and financial motivations (incentives) for women trained before employment.Regarding state employment programs, Israel has different employment programs for both women and men, but the gender perspective is also integrated into this direction.The phenomenon of the Comptroller General provided by the record of Section 304 of the General Provisions of the United States Retirement Equity Act of 1984 is significant for Georgia in the process of implementing pension reform. In order to protect the rights of the vulnerable group in old age - elderly (older) women - it is necessary to study the impact of pension plans on women.SEC. 304. STUDY BY COMPTROLLER GENERAL OF THE UNITED STATES.GENERAL RULE.—The Comptroller General of the United States shall conduct a detailed study (based on a reliable scientific sample of typical pension plans of various designs and sizes) of the effect on women of participation, vesting, funding, integration, survivorship features, and other relevant plan and Federal pension rules.".[18] A life-cycle approach is a useful strategy for addressing complex discrimination based on gender and age. This is used in the Beijing Platform for Action to examine the spread and incidence of discriminatory practices that affect women at different stages of their lives and development. A life-cycle approach analyses discrimination in terms of the accumulation of forms of discrimination that may affect different stages of a person's life and, at the same time, considers the positive contribution made by employees to society at different stages. The positive contribution also includes the unpaid care work of employed women. It is a fact that the life cycle approach has a 'helping function'; in particular, it helps to ensure that the discrimination a woman faces at one stage of her life will not continue into later stages (ILO, Gender Promotion Programme, 2001).The vision of the modern world’s attitude when discussing the rights of older people is well seen in the work of Julie Childs: Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention. "[19], which will be reviewed below. The world's older (elder) population is growing at an unprecedented rate. About 8.5% of the world's people (617 million) are over 65 years old. According to a 2015 United Nations report, this percentage is forecasted to increase to nearly 17% of the world's population, or 1.6 billion, by 2050.[20] “The ageing population is growing at a rapid rate, stressing resources and spurring resentments that could lead to elder abuse. A convention on elder rights could mitigate the impact by providing a framework to manage the confluence of global modernisation, ageing, and demographic changes.”[21] It is necessary for developing countries to face the reality that 1.7 billion people over the age of 60 - almost more than 80% of the world's elderly population - will live in less-developed regions in 2050.[22] The need for laws to protect the older population cannot be ignored, and it is too important to rely solely upon moral standards and cultural codes of conduct. Moreover, older persons need to have a say in these decisions.[23] An article by Julie Childs - Consultant to the United States Department of Justice Elder Justice Initiative, discusses ways to determine whether the rights of older people are human rights that international treaties should protect. The expert expands the discussion on how we can best protect the rights of the elderly (aged, senior people).The Universal Declaration of Human Rights (UDHR) is one of the most recognised and influential agreements.[24] The UDHR was adopted by the UN General Assembly in 1948 and provides that human rights impose obligations on the state to ensure just and fair treatment of its citizens. The UDHR consists of thirty articles that affirm the rights of the individual. These rights are not legally binding per se but are described in subsequent international treaties, regional human rights instruments, national constitutions, and laws. "In addition to the UDHR, there are several other cross-cutting UN human rights treaties that generally moved human rights issues forward, but few that focus on protecting elder rights."[25] For example, the Madrid International Plan of Action on Ageing ("MIPAA") was adopted at the Second World Assembly on Ageing in April 2002.[26] MIPAA created a new stage for the protection of the rights of the elderly. According to MIPAA, the world's main challenge is "building a society for all ages". "The MIPAA plan of action focused on three priority areas: "older persons and development; advancing health and well-being into old age; and ensuring enabling and supportive environments." Significantly, it was the first time governments agreed to connect ageing to human rights as a central issue at the UN conferences and summits."[27] In 2009, the Committee on Economic, Social and Cultural Rights ("CESCR") identified age as one of the prohibited grounds of discrimination.[28] CESCR is a "UN body - composed of 18 independent experts that monitor the implementation of the International Covenant on Economic, Social and Cultural Rights by its member states“.[29] CESCR has emphasised the need to prohibit age discrimination in finding work and vocational training (more focusing on people living in poverty) and to address the issue of unequal access to pensions.[30] The International Covenant on Economic, Social, and Cultural Rights stipulates that states are obliged to progressively implement the right to social security for all individuals within their territories. In 2010, the UN’s General Assembly established the Open-Ended Working Group on Ageing ("OEWG") to examine the treatment and behaviour towards the aged population. The OEWG continues to study international human rights.[31] The need to regulate the rights of the elderly at the legislative level is slowly becoming evident.Latin America has been a constant supporter of the protection of the rights of the elderly, and on June 15, 2015, the Americas became the first region in the world to have an instrument for the promotion and protection of the rights of the elderly.[32] The Organization of American States ("OAS"), with the support of the Pan American Health Organization ("PAHO"), adopted the Inter-American Convention on Protecting the Human Rights of Older Persons.[33] The Convention on the Protection of Older Persons ("CPHROP") recognises that older people can and should freely use all human rights and fundamental freedoms.[34] The Convention, which was signed by the governments of Argentina, Brazil, Chile, Costa Rica, and Uruguay, is an important catalyst for other countries to establish appropriate normative framework laws for the protection of old age.“What Are Elder Rights and Why We Make Special Efforts to Protect Them?[35]As human rights go, elder rights do not, in and of themselves, appear so extraordinary. For example:[36]the right to work and to pursue other income-generating opportunities with no barriers based on age;to retire and participate in determining when and at what pace withdrawal from the labour force takes place. To permit informed planning and decision-making;to live in safe and adaptable environments to personal preferences and changing capacities. To reside at home for as long as possible;to remain integrated and participate actively in society, including the development process and formulation and implementation of policies that directly affect their well-being;to be valued independently of their economic contributions. To live in dignity and security and to be free of exploitation and physical or mental abuse.”[37]Young women and men and employees of all ages need work-family balance policies. The ability of employed older women to earn a living wage for themselves and other vulnerable family members depends on work-family balance policies and the availability of jobs.[38]There are several factors that have a more negative impact on older working women. In particular:age discrimination at work, which means: the imposition of age restrictions for employment or training;indirect discrimination through measures that force older workers to retire early, such as compulsory retirement savings schemes.[39]Although, according to actuarial calculations, women live longer than men, the main obstacle to receiving an equivalent pension is that women may not be able to pay the contributions to pension schemes continuously, or they may not reach the minimum amount of earnings during their lifetime.[40]Despite their common denominators concerning basic human rights in general, the reason why we must address the rights of the elderly separately and protect them uniquely is the systematic discrimination against older people at the individual, institutional and societal levels that impede, undermines, and in some cases destroys basic human rights.[41] "This is the necrotic power of ageism." Another false assumption characteristic of ageing (ageism) is that older people are a monolithic group.[42] Ageing may be the common denominator, but the counters are as infinite as the variations in culture and experience when reflecting on human history.[43] The assumption that all members of a group, such as the elderly, are the same creates a dangerous threat to the full protection of their rights. Each older person should enjoy these rights individually and may even be different. The chances of protecting the rights of the elderly are also reduced when a society confuses the elderly with the sick, weak, or disabled. A survey in Ireland found that the most common form of ageism was the attribution of age-related illnesses by health workers as a consequence of age.[44] “Perhaps the most insidious manifestation of ageism on elder rights is the misperception that older adults are a cohort of frail, burdensome, demented people”.[45] For example, in 2016, in the "World Values Survey" analysed by the World Health Organization, 60% of respondents said that older people were not respected.[46] Other studies have shown that even healthcare providers' attitudes "are shaped by the persistent misconception that elderly patients are frail, demented, and have little chance of survival."[47] This stereotype can harm the standard of health and life. Isolation and marginalisation can also leave older people vulnerable to elder abuse.[48] English Longitudinal Study (ELSA) of Ageing Final Report[49] examined the social exclusion of older people and identified seven different dimensions of social exclusion: social relations, cultural activities, civic activities, access to basic services, neighbourhood exclusion, financial products, and material goods.Conclusion“If you can't measure it, you can't manage it" - Management Consultant Peter Ferdinand Drucker.[50]According to the International Bill of Human Rights, the right to health is closely related to the realisation of other human rights, including rights such as Food, housing, work, education, human dignity, life, non-discrimination, equality, prohibition of torture, privacy, access to information, freedom of association, assembly and movement. These and other rights and freedoms are related to the components of the right to health.[51]As a result of gender inequality, social consequences caused by existing stereotypes about older women, unfair distribution of resources, and lack of state employment policy for older women are against the 2030 Agenda of the United Nations for Sustainable Development goals. Therefore, it is better to understand this gap and further eliminate it, which will regulate and increase the potential contribution of older women in public life.[52]These are the four pillars of the Forum’s gender gauge (economic participation and opportunity, education, health and political empowerment).[53] "...respect for the individual and his dignity is expressed through the freedom of the individual regarding the choice to work while emphasising the importance of work for personal development as well as for social and economic inclusion". Since there is a high increase in the informal economy (informal jobs) in Georgia, first of all, we should examine the statistical data about the exact number of people working in the informal economy, and in parallel with this process, the working conditions of the employees in the above-mentioned economy should be monitored. After that, the government should take care of the legal regulation (amendments to the labour code) that will regulate the working conditions of those employed in the informal economy.[54]The state should designate an agency with an audit function to conduct a detailed study (based on a reliable scientific sample of typical pension plans of various designs and sizes) on women's participation, funding, integration, survival characteristics, and other relevant plans and the impact of state/cumulative pensions.For citizens of retirement age to select state aid and benefits in a relevant and targeted manner, it is better to amend the Law of Georgia on State Pensions to create age categories. Thus, it will be possible to introduce a new term - "older". Two baskets will be taken into account: Basket I - category of 60 to 70-year-olds; II basket - category of eldest over 70 years old. The specified baskets will help the government to plan appropriately targeted state policies. For example, the issue of professional training will be included in the basket of the older people (elderly), and at the same time, in the basket of the eldest - attention will be paid to the issue of social security.[55]“The Assembly, generously and capably hosted by the Government of Spain, showed the United Nations playing its essential role of putting tomorrow’s issues on today’s agenda. However, the real test will be implementation. Each and every one of us, young and old, has a role to play in promoting solidarity between generations, in combating discrimination against older people, and in building a future of security, opportunity and dignity for people of all ages”. - Kofi A. Annan[56]BibliographyReferences in the Georgian LanguageBatiashvili I., Myth of older women and world’s stereotypes, Law and World, N17, 2021, 64, 68.United Nations, Universal Declaration of Human Rights, 60th Anniversary Special Edition 1948 -2008, Georgia's Office of the United Nations Public Information Department, Office of the United Nations High Commissioner for Human Rights, Georgia, DPI/876/Rev.4-07-55693/, 2008.Law of Georgia "On State Pensions", 2442, Parliament of Georgia, 23/12/2005, Chapter II, Article 5.Batiashvili I., "Decent Living and Employment of Older Women", materials of the international scientific conference, challenges of modern law, "World of Lawyers" publishing house, Tbilisi, 2022.References in a Foreign LanguageUnited Nations, The Universal Declaration of Human Rights, United Nations General Assembly, 1948.United Nations International Research and Training Institute for the Advancement of Women (INSTRAW) "Ageing in Gendered World: Women's Issues and Identities", Santo Domingo, Dominican Republic, 1999, VII.World Health Organization, executive summary women and health Today's evidence tomorrow's Agenda, 2009, Geneva, 1-4.Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfнационального страхованияhttps://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/HatavotLenashimMuvtalot.aspxКнессет, Закон о национальном страховании [комбинированная версия], 5755–1995 гг, Глава 7 - Страхование по безработице, חוק הביטוח הלאומי )נוסח משולב(, התשנ"ה- 1, פרק ז': ביטוח אבטלה, https://www.btl.gov.il/Laws/Pages/LawsList.aspx (ეროვნული დაზღვევის კანონი (ინტეგრირებული ვერსია), 5755-1)национального страхованияhttps://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/halaatGilPrishaLenashim.aspxМинистр социального равенства, Руководство для пожилых граждан Израиля права, льготы и информация, *8840, 2015, 34,https://www.gov.il/BlobFolder/guide/benefits_shvyon/he/%D7%94%D7%9E%D7%93%D7%A8%D7%99%D7%9A%20%D7%9C%D7%90%D7%96%D7%A8%D7%97%20%D7%94%D7%95%D7%95%D7%AA%D7%99%D7%A7%20-%20%D7%A8%D7%95%D7%A1%D7%99%D7%AA.pdfнационального страхованияhttps://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/HaalatSchumHaachnasa.aspx ; https://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/halaatGilPrishaLenashim.aspxнационального страхования,https://www.btl.gov.il/RussianHomePage/Benefits_ru/Yeladim_ru/Pages/default.aspxCommittee on Economic, Social and Cultural Rights, UNITED NATIONS HUM. RTs. OFF. OF THE HIGH COMM'R, http://www.ohchr.org/en/hrbodies/cescr/pages/cescrindex.aspx (last visited Mar. 11, 2020). ("The Committee was established under [United Nations Economic and Social Council ("ECOSOC")] Resolution 1985/17 of 28 May 1985 to carry out the monitoring functions assigned to the [ECOSOC] in Part IV of the Covenant."). The main function of the CESCR is to oversee the covenant implementation by state parties. See UN Committee on Economic, Social and Cultural Rights (CESCR), ECOINET, https://www.ecoi.net/en/source/11512.html (last updated Aug. 30, 2018). The committee strives to hold constructive discussions with state representatives regarding the application of the terms of the covenant. Id. The committee also assists governments in fulfilling their responsibilities under the covenant through policy and legislation aiming to secure and protect social, economic, and cultural privileges. Id. https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfUnited Nations, Compilation of General Comments and General Recommendations Adopted by Human Rights Treaty Bodies, General Comment No.14, para.3, p.87, HRI/GEN/1/Rev.8 8 May 2006.Committee on Economic, Social and Cultural Rights, general comment No. 18 https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfUnited Nations, the Madrid International Plan of Action on Ageing and the Political Declaration, Second World Assembly on Ageing, Spain, 2002.Committee on Economic, Social and Cultural Rights, general comment No. 18.United Nations, Compilation of General Comments and General Recommendations Adopted by Human Rights Treaty Bodies, General Comment No.14, para.3, p.87, HRI/GEN/1/Rev.8 8 May 2006.Discrimination and negative attitudes about ageing are bad for your health, WORLD HEALTH ORG. (Sep. 29, 2016), https://www.who.int/news-roori/detail/29-09-2016-discrimination-and-negative-attitudes-about-ageing-are-bad-for-your-health. https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfThe Social Exclusion of Older People: Evidence from the First Wave of the English Longitudinal Study of Ageing Final Report, OFF. OF THE DEP. PRIME MINISTER 15-17 (Matt Barnes ed., 2006), https://www.researchgate.net/publication/37183878_The_social_exclusion_of_older_people_evidence_from_the_first_wave_of_the_English_Longitudinal_Study_of_Ageing_ELSA_final_Report, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfTova Band-Winterstein, Health Care Provision for Older Persons: The Interplay Between Ageism and Elder Neglect, 34:3 J. OF APPLIED GERONTOLOGY 113, 114 (2015), https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfDiane E. Rykken, Sex in the Later Years, in THE ELDERLY AS MODERN PIONEERS, 162 (Philip Silverman ed., 1987), https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfSee The Independent Expert on the Enjoyment of All Human Rights by Older Persons, UNITED NATIONS HUM. RTs. OFF. OF THE HIGH COMM'R, http://www.ohchr.org/EN/Issues/ OlderPersons/IE/Pages/IEOlderPersons.aspx (last visited Mar. 11, 2020) ("In May 2014, the Human Rights Council appointed Ms Rosa Kornfeld-Matte as the first Independent Expert on the enjoyment of all human rights by older persons."), https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfInter-American Convention on Protecting the Human Rights of Older Persons, June 15, 2015, O.A.S.T.S. A-70,https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdfRetirement Equity Act of 1984, Pub. L. No. 98-397, 98 Stat. 1426, Title III, General Provisions, https://www.congress.gov/bill/98th-congress/house-bill/4280/text24. ILO ABC of women workers’ rights and gender equality, Geneva, International Labour Office, 2000, Second edition 2007, 146-148. Footnotes[1] Moseley-Braun, C. (1996). Women's Retirement Security. Elder Law Journal, 4(2), 493-498.[2] Ibid.[3] United Nations, the Universal Declaration of Human Rights, United Nations General Assembly, 1948. [4] United Nations, Universal Declaration of Human Rights, 60th Anniversary Special Edition 1948 -2008, Georgia's Office of the United Nations Public Information Department, Office of the United Nations High Commissioner for Human Rights, Georgia, DPI/876/Rev.4-07-55693/, 2008.[5] Batiashvili I., "Decent Living and Employment of Older Women", materials of the international scientific conference, challenges of modern law, "World of Lawyers" publishing house, Tbilisi, 2022.[6] Ibid.[7] United Nations International Research and Training Institute for the Advancement of Women (INSTRAW) "Ageing in Gendered World: Women's Issues and Identities", Santo Domingo, Dominican Republic, 1999, VII.[8] www.101healthportal.com[9] World Health Organization, executive summary women and health Today's evidence tomorrow's Agenda, 2009, Geneva, 1-4.[10] Ibid.[11] Batiashvili I., Myth of elder women and world’s stereotypes, Law and World, N17, 2021, 64, 68.[12] Law of Georgia "On State Pensions", 2442, Parliament of Georgia, 23/12/2005, Chapter II, Article 5.[13] национального страхования https://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/HatavotLenashimMuvtalot.aspx[14]Кнессет, Закон о национальном страховании [комбинированная версия], 5755–1995 гг, Глава 7 - Страхование по безработице, חוק הביטוח הלאומי )נוסח משולב(, התשנ"ה- 1, פרק ז': ביטוח אבטלה, https://www.btl.gov.il/Laws/Pages/LawsList.aspx (ეროვნული დაზღვევის კანონი (ინტეგრირებული ვერსია), 5755-1)[15] Министр социального равенства, Руководство для пожилых граждан Израиля права, льготы и информация, *8840, 2015, 34, https://www.gov.il/BlobFolder/guide/benefits_shvyon/he/%D7%94%D7%9E%D7%93%D7%A8%D7%99%D7%9A%20%D7%9C%D7%90%D7%96%D7%A8%D7%97%20%D7%94%D7%95%D7%95%D7%AA%D7%99%D7%A7%20-%20%D7%A8%D7%95%D7%A1%D7%99%D7%AA.pdf[16] национального страхования https://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/HaalatSchumHaachnasa.aspx ; https://www.btl.gov.il/RussianHomePage/Benefits_ru/Vatikim_ru/IdkunimEzracjVatik2022/Pages/halaatGilPrishaLenashim.aspx[17]национального страхования, https://www.btl.gov.il/RussianHomePage/Benefits_ru/Yeladim_ru/Pages/default.aspx[18] Retirement Equity Act of 1984, Pub. L. No. 98-397, 98 Stat. 1426, Title III, General Provisions, https://www.congress.gov/bill/98th-congress/house-bill/4280/text[19] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online.[20] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf Id. According to the National Institute on Aging ("NIA") and National Institutes of Health ("NIH"), the older demographic is rapidly growing in proportion the rest of the global population. See id. The growing population of older people around the world must be the impetus for ensuring the health, livelihood, and rights of our elders; the NIH and the US Census Bureau are collaborating to ensure that data collected is used to "better understand the course and implications of population aging." Id.World's Older Population Grows Dramatically, NAT'L INST. OF HEALTH (March 28, 2016), https://www.nih.gov/news-events/news-releases/worlds-older-population-growsdramatically. [21] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online. https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[22] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf World Population Ageing, supra note 2, at 9.[23] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online. https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[24] G.A. Res. 217 (III) A, U.N. SCOR, Universal Declaration of Human Rights, U.N. Doc. A/RES/217(JJ) (Dec. 10, 1948)[25] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online.[26] U.N. Assembly on Ageing, 2 nd Sess., Political Declaration and Madrid International Plan of Action on Ageing (Apr. 12, 2002), available at https://www.un.org/enl/events/pastevents/pdfs/Madrid-plan.pdf[27] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[28] C.E.S.C.R., 4 2nd Sess., General Comment No. 20: Non-discrimination in Economic, Social and Cultural Rights (art. 2, para. 2, of the International Covenant on Economic, Social and Cultural Rights) 29, U.N. Doc. E/C. 12/GC/20 (July 2, 2009), https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[29] Committee on Economic, Social and Cultural Rights, UNITED NATIONS HUM. RTs. OFF. OF THE HIGH COMM'R, http://www.ohchr.org/en/hrbodies/cescr/pages/cescrindex.aspx (last visited Mar. 11, 2020). ("The Committee was established under [United Nations Economic and Social Council ("ECOSOC")] Resolution 1985/17 of 28 May 1985 to carry out the monitoring functions assigned to the [ECOSOC] in Part IV of the Covenant."). The main function of the CESCR is to oversee the covenant implementation by states parties. See UN Committee on Economic, Social and Cultural Rights (CESCR), ECOINET, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf https://www.ecoi.net/en/source/11512.html (last updated Aug. 30, 2018). The committee strives to hold constructive discussions with state representatives regarding application of the terms of the covenant. Id. The committee also assists governments in fulfilling their responsibilities under the covenant through policy and legislation aiming to secure and protect social, economic, and cultural privileges. Id.[30] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[31] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf See the Independent Expert on the Enjoyment of All Human Rights by Older Persons, UNITED NATIONS HUM. RTs. OFF. OF THE HIGH COMM'R, http://www.ohchr.org/EN/Issues/ OlderPersons/IE/Pages/IEOlderPersons.aspx (last visited Mar. 11, 2020) ("In May 2014, the Human Rights Council appointed Ms. Rosa Kornfeld-Matte as the first Independent Expert on the enjoyment of all human rights by older persons.").[32] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online.[33] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf Inter-American Convention on Protecting the Human Rights of Older Persons, June 15, 2015, O.A.S.T.S. A-70.[34] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[35] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[36] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[37] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[38] ILO ABC of women workers’ rights and gender equality, Geneva, International Labour Office, 2000, Second edition 2007, 146-148.[39] Ibid.[40] Ibid.[41] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf (Tova Band-Winterstein, Health Care Provision for Older Persons: The Interplay between Ageism and Elder Neglect, 34:3 J. OF APPLIED GERONTOLOGY 113, 114 (2015)).[42] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[43] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf (Diane E. Rykken, Sex in the Later Years, in THE ELDERLY AS MODERN PIONEERS, 162 (Philip Silverman ed., 1987)).[44] https://www.stetson.edu/law/agingjournal/media/ JCIALP%20Vol%2011%20(Final).pdf[45] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online.[46] https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf Discrimination and negative attitudes about ageing are bad for your health, WORLD HEALTH ORG. (Sep. 29, 2016), https://www.who.int/news-roori/detail/29-09-2016-discrimination-and-negative-attitudes-about-ageing-are-bad-for-your-health.[47] Childs, J. "Elder Rights Are Not Nesting Dolls: An Argument for an International Elder Rights Convention." Journal of Comparative and International Aging Law & Policy, 11, 2020, p. 141-170. Hein Online, https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[48] Ibid.[49] The Social Exclusion of Older People: Evidence from the First Wave of the English Longitudinal Study of Ageing Final Report, OFF. OF THE DEP. PRIME MINISTER 15-17 (Matt Barnes ed., 2006), https://www.researchgate.net/publication/37183878_The_social_exclusion_of_older_people_evidence_from_the_first_wave_of_the_English_Longitudinal_Study_of_Ageing_ELSA_final_Report https://www.stetson.edu/law/agingjournal/media/JCIALP%20Vol%2011%20(Final).pdf[50] https://www.weforum.org/agenda/2022/03/international-womens-day-gender-gap-inequality/[51] United Nations, Compilation of General Comments and General Recommendations Adopted by Human Rights Treaty Bodies, General comment No.14, para.3, p.87.[52] Batiashvili I., "Decent Living and Employment of Older Women", materials of the international scientific conference, challenges of modern law, "World of Lawyers" publishing house, Tbilisi, 2022.[53] World Economic Forum, Global Gender Gap Report 2021, INSIGHT REPORT, MARCH 2021, 198, https://www.weforum.org/reports/global-gender-gap-report-2021[54] Batiashvili I., "Decent Living and Employment of Older Women", materials of the international scientific conference, challenges of modern law, "World of Lawyers" publishing house, Tbilisi, 2022.[55] Ibid.[56] United Nations, The Madrid International Plan of Action on Ageing and the Political Declaration, Second World Assembly on Ageing, Spain, 2002.